A review of Islamic banks financing in Malaysia - Mohd Daud, Mohd Ariff; Abd Sukor, Mohd Edil; Musa, Muhammad Adli; Abrahan, Amni Suhailah; Wan Jusoh, Wan Noor Hazlina (Malaysian Consumer and Family Economics Association, 2023)
This study aims to investigate the financing behavior of Islamic banks in Malaysia by examining the concepts, types, purposes, and sectors of financing that Islamic banks provide. How Islamic banks behave, whether they are full-fledged Islamic banks or subsidiaries, is also examined. In addition, this study also xplores the ethicality of providing non-productive financing. This study utilizes data from Bank Negara Malaysia, along with annual reports of individual Islamic banks in Malaysia. The findings indicate that the financing behavior of Islamic banks is nearly identical to those of their conventional counterparts, in which debt-based financing instruments are widely employed, and that the allocation of financing is predominantly for activities that can be deemed as non-productive. This study contributes to the discourse on financial ethics concerning the financing behavior of Islamic banks, which is currently quite limited. It is anticipated that this research would potentially initiate more discussions on the ethicality of Islamic banks and improve current practices.